Markups in a dual labour market: The case of the Netherlands - Gerrit Hugo van Heuvelen; Leon Bettendorf; Gerdien Meijerink (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
We follow the production function approach to assess markups, which requires the estimation of the output elasticity of a free input. In the basic setup we estimate a structural value added production function, using temporary contract hours as free input. We find rather stable markups in the Netherlands in the period 2006-2016. We show that extending the free variable incorrectly with fixed contract hours results in an increasing markup. Findings are robust to an alternative setup, in which a gross output function is specified and materials are used as free input. Implications for applied work and policy are discussed.
Keywords: 330; markups; free variable; flexible contract labour